2016
DOI: 10.1093/cid/ciw086
|View full text |Cite
|
Sign up to set email alerts
|

Streamlining Screening to Treatment: The Hepatitis C Cascade of Care at Kaiser Permanente Mid-Atlantic States

Abstract: Hepatitis C virus (HCV) screening is recommended for patients at risk and/or born during , but screening gaps persist. This new program screens target populations and enhances care linkage for chronically HCV-infected patients. Kaiser Permanente Mid-Atlantic States created a comprehensive HCV screening pathway, supported by a HCV care coordinator. The testing pathway includes HCV antibody (Ab), automatic HCV RNA for Ab-positive patients, coinfection and liver health tests, vibration-controlled transient elasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 29 publications
4
46
1
Order By: Relevance
“…Although, HCV RNA and genotype testing rates have improved in recent years and are similar to those reported for HCV positive Veterans and Kaiser Permanente members in the United States (95%) and higher than for primary care in Canada and United States (47.0% to 60.9%), there is a further need to reduce the gap between those antibody diagnosed and those undergoing further testing (Maier et al, 2016, Jonas et al, 2016, Spradling et al, 2014, Viner et al, 2015). We demonstrated that people with high risk activities progress to RNA testing while men and older cohorts, especially those born in 1945–64 lacked RNA testing (Spradling et al, 2014, Cachay et al, 2014).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Although, HCV RNA and genotype testing rates have improved in recent years and are similar to those reported for HCV positive Veterans and Kaiser Permanente members in the United States (95%) and higher than for primary care in Canada and United States (47.0% to 60.9%), there is a further need to reduce the gap between those antibody diagnosed and those undergoing further testing (Maier et al, 2016, Jonas et al, 2016, Spradling et al, 2014, Viner et al, 2015). We demonstrated that people with high risk activities progress to RNA testing while men and older cohorts, especially those born in 1945–64 lacked RNA testing (Spradling et al, 2014, Cachay et al, 2014).…”
Section: Discussionmentioning
confidence: 69%
“…Although guidelines and education for primary care physicians are important instruments to bridge this gap, a single blood sample test strategy in which those testing positive for antibody are also tested for RNA (reflex testing) and possibly for genotype could be an effective structural intervention to bridge this gap. Reflex testing for RNA has been implemented in the VA system and recently in Kaiser Permanente system, and was associated with higher RNA testing rates (Maier et al, 2016, Jonas et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The EHR intervention increased HCV screening similarly to electronic interventions in other studies [9, 10]. The simplicity and low cost of the EHR intervention and widespread use of EHR systems with health maintenance reminders or other CDS tools suggests that our EHR intervention may work across different health systems.…”
Section: Discussionmentioning
confidence: 70%
“…Jonas et al [9] described a prevalence of 3.25% in a Kaiser Permanente cohort from Maryland, Virginia, and the District of Columbia, and Goel et al [12] described a prevalence of 3.3% in a New York City university-based primary care cohort of persons born between 1945 and 1965; both groups showed a greater proportion of black and Hispanic patients. A review of HCV seroprevalence in state prisons showed a wide range of seroprevalence from 7.5% to 41.2% between states, and the prevalence among Hispanic subpopulations also varies by Hispanic/Latino background and city, with the highest prevalence described in the Bronx and lower prevalence in Chicago, Miami, and San Diego [3, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous prior studies evaluating routine HIV and HCV testing initiatives in primary care settings have found that such efforts increase testing and can lead to large numbers of persons being screened [15–20]. However, data evaluating the impact of routine testing on HIV and HCV case finding, the outcome of greater importance, are more limited.…”
Section: Discussionmentioning
confidence: 99%